Social Capital Impact on Quality of Life of Low-Income Population Group - Amin, Aziz; Puad Mat Som, Ahmad; Zolkifeli, Zainul (International Journal of Engineering and Technology, 2018)
Efforts to improve the quality of life are often the goals of development programs in every country, Malaysia is no exception. Various policies and programs have been conducted to ensure the quality of life of the community to be at a high level. Each country has its own resources in the form of raw materials, investments, labor and so on. Social capital is one of the resources in a country. Thus, this study is conducted to identify the impact of social capital on respondents' quality of life. This study focuses on the low income group of bottom 40 per cent of the population, so-called B40 as respondents. Surveys were conducted to 100 household heads in Kuala Terengganu, Terengganu, Malaysia. SPSS software has been used to analyze the data that was collected. The findings show that social capital is able to influence the respondents' quality of life. Therefore, each program or policy framework should be in line with the needs of social capital constructs to impact quality of life of the society.Â Â